Resistance training mitigates hepato-cardiac changes and muscle mitochondrial protein reductions in rats with diet-induced obesity - Laurindo, Caroline Pancera [UNESP]; Rego Gregorio, Karen C. [UNESP]; Rippi Moreno, Ana Caroline [UNESP]; Viudes Agostinho, Julia Maia [UNESP]; Campos, Evelyn Carvalho [UNESP]; Nai, Gisele Alborghetti; Nunes, Maria Tereza; Seraphim, Patrícia Monteiro [UNESP] (Elsevier, 2021)
Aim: To investigate the effect of resistance training (RT) on hepatocardiovascular and muscle mitochondrial parameters in rats that were fed a high-calorie diet for 12 weeks. Main methods: The animals were divided into four groups: control (C), exercise (E), obese (O), and obese plus exercise (OE). Group E and OE rats performed resistance training by climbing on a vertical ladder with load attached to the end of the tail (1×/day, 3×/week, for 12 weeks). Group O and OE rats were fed a high-calorie diet containing chow and a cafeteria diet for 12 weeks. Under anesthesia, the heart and liver were removed for histopathological analysis, and the gastrocnemius muscle was removed for Western blotting. Key findings: Group O rats were heavier, with increased fat mass, elevated fasting glycemia, and total triglycerides, and exhibited a significant number of Kupffer cells and diffuse steatosis in the liver. Group O rats also showed increased thickness of the right ventricle, septum, and pulmonary artery. All of these parameters were attenuated by RT. PGC1-α protein levels were increased in both exercise groups. The protein levels of OXPHOS complexes III, IV, and V were reduced in Group O, while RT prevented this alteration. Significance: RT exerts a protective effect against hepato-cardiac alterations and prevents changes in the muscle mitochondrial protein profile induced by a high-calorie diet.
Keywords: Hepato-cardiac alterations; Mitochondrial biogenesis; Obesity; Resistance training